Comparison between Immediate Effects of Post Isometric Relaxation and Reciprocal Inhibition Techniques on Hamstring Flexibility in Patients with Hamstring Tightness: An Experimental Study - Samiksha Sanjiv Sathe1 , Tejal Rajandekar2 , Kirti Thodge3 , Ashwin Chavhan4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim: There are studies comparing the effects of post isometric relaxation technique & reciprocal inhibitiontechnique on hamstring muscle flexibility but to the best of our knowledge there is hardly any study that hasreported comparative immediate effect of these two techniques. Thus the aim of our study was to evaluatethe immediate effect of these two techniques on hamstring muscle flexibility.Method: The research design used was Comparative Experimental study design. Total 46 participants werescreened and those meeting the inclusion criteria (n=40) were included in the study. The participants wererandomly divided into two groups- group A - post isometric relaxation and Group B - reciprocal inhibitionof 20 each. Pre and immediate post intervention scores were measured in terms of AKETFindings: Inter group comparison (student’s unpaired t test) showed that there was no statistically significantdifference between the two groups in terms of AKET. The comparison of pre and post intervention values ofthe outcome measure in both the groups showed a statistically significant difference.Conclusion: It can be concluded from the present study that both post isometric relaxation technique &reciprocal inhibition technique have an immediate effect on reducing hamstring muscle tightness. Fromthe mean difference values it is visible that PIR (13.20) is slightly more effective than RI (5.45) althoughstatistically significant difference is not seen.